Character appearance in hologram tutors: Unveiling valence and learning enjoyment dynamics - Ahmad Zamzuri Bin Mohamad Ali (Tanjung Malim, 2024)
Character appearance in hologram tutors: Unveiling valence and learning enjoyment dynamics by Ahmad Zamzuri Bin Mohamad Ali